2021
DOI: 10.1371/journal.pone.0252190
|View full text |Cite
|
Sign up to set email alerts
|

Versatile artificial mer operons in Escherichia coli towards whole cell biosensing and adsorption of mercury

Abstract: Mercury exists naturally and mainly as a man-made pollutant in the environment, where it exerts adverse effects on local ecosystems and living organisms. It is important to develop an appropriate synthetic biological device that recognizes, detects and removes the bioavailable fraction of environmental mercury. Both single-signal and double-signal output mercury biosensors were assembled using a natural mer operon as a template. Selectivity and sensitivity of whole-cell biosensors based on artificial mer opero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 44 publications
(102 reference statements)
0
21
1
Order By: Relevance
“…No continuous increase in the biosensing signals was observed in previously developed CadR-based biosensors within non-cytotoxic concentration of cadmium exposure ( Tao et al, 2013 ; Guo et al, 2021 ). The saturation of metal-binding sites of low-level-background-expressed CadR may be the underlying cause, and it is very common in other developed biosensors using MerR-like regulators ( Joe et al, 2012 ; Guo et al, 2019a ; Hui et al, 2020a ; Zhang et al, 2021 ). Furthermore, the accumulation of red fluorescent protein mCherry responsive to above 50 μM Cd(II) ( Figure 4D ) can be obviously distinguished by the naked eye when compared with the accumulation of green fluorescent protein eGFP ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No continuous increase in the biosensing signals was observed in previously developed CadR-based biosensors within non-cytotoxic concentration of cadmium exposure ( Tao et al, 2013 ; Guo et al, 2021 ). The saturation of metal-binding sites of low-level-background-expressed CadR may be the underlying cause, and it is very common in other developed biosensors using MerR-like regulators ( Joe et al, 2012 ; Guo et al, 2019a ; Hui et al, 2020a ; Zhang et al, 2021 ). Furthermore, the accumulation of red fluorescent protein mCherry responsive to above 50 μM Cd(II) ( Figure 4D ) can be obviously distinguished by the naked eye when compared with the accumulation of green fluorescent protein eGFP ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have demonstrated that metalloregulator MerR responded selectively to Hg(II). MerR-based whole-cell biosensors all showed extraordinary selectivity toward Hg(II) ( Hansen and Sorensen, 2000 ; Wang et al, 2020 ; Zhang et al, 2021 ). If CadR-based biosensing system and MerR-based biosensing system are integrated into one genetic construct, the resultant dual-sensing biosensor will be able to distinguish Cd(II) and Hg(II) simultaneously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The response strength of whole-cell biosensor was determined by both the response rate of the sensing element and the maturation time of the reporter product (Bereza-Malcolm et al 2015;Hansen and Sorensen 2000;Zhang et al 2021). To find the suitable induction time for the two kinds of indigoidinebased biosensors, exponential-phase TOP10/pPmer-ind and TOP10/pPpbr-ind were exposed to 1 μM Hg(II) and 30 μM Pb(II), respectively.…”
Section: Response Characteristics Of the Indigoidine-based Biosensors Toward Target Heavy Metal Ionsmentioning
confidence: 99%
“…The extraordinary fidelity, sensory, and regulatory capacities of MerR family regulators have made them as a source of powerful biological parts for the assembly of whole-cell biosensors (Jung and Lee 2019). Among MerR family proteins, well-characterized MerR, PbrR, and CadR have been used as sensing modules to develop many classical heavy metal biosensors, and the output modules containing luciferase, fluorescent protein, and β-galactosidase were usually inserted downstream of the promoter/operator region to replace the detoxification genes (Bereza-Malcolm et al 2016;Cai et al 2018;Guo et al 2019a;Guo et al 2021;Hansen and Sorensen 2000;Kumar et al 2017;Zhang et al 2021). The resultant output signals including luminescence, fluorescence, and enzymatic activity can be detected quantitatively by various types of spectrophotometers.…”
Section: Introductionmentioning
confidence: 99%